O conselho escolar como espaço de participação: uma reflexão sobre a prética nas escolas públicas estaduais do município de Fortaleza - Carneiro, Maria Joyce Maia Costa (2005)
This work has as interest to verify the participation of the Pertaining to school Council in the CERE Profª Mª José Santos Ferreira Gomes and in the EEFM Antonio Bezerra of 3ª Region of the CREDE 21. The study object says respect to the performance of the Pertaining to School Council who adds the diverse representative segments of the Pertaining to school unit, reflecting on the impediments chokes of its effective functioning. The theoretical and methodological referential was based in authors as: Carvalho (2000), Arroyo (1979), Freire (1997), Gadotti (2000), Lück (1998), Paro (1997) and Libâneo (1984). The collection of data if gave with the use of 154 questionnaires that had been answered by 49 professors, 45 students, 40 parents and 20 employees. We still carry through two Focal Groups with representatives of the parents of the two schools. The results shows that it does not have significant differences in the performance of both the Council, limiting it a restricted participation to the functions administrative and financial, in detriment of excessively. We perceive that the parents believe the performance of the Advice, despite the little evolvement. The questionnaires indicate them that the diverse pertaining to school segments of EEFMAB and CERE deposit confidence in the work of the Council, recognizing that exactly still taking advantage one politics of central character, the school earned with its implantation. For us, still necessary a bigger joint between the SEDUC and the schools in the direction to promote the active participation and politics of the community.